2015
DOI: 10.1039/c5pp00079c
|View full text |Cite
|
Sign up to set email alerts
|

From intra- to inter-molecular hydrogen bonds with the surroundings: steady-state and timeresolved behaviours

Abstract: The proposed photodynamic mechanisms for 6A-HBO at the femtosecond-picosecond scale in a DMF solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Detailed NMR data of 1 – 3 are provided in the experimental section and NMR spectra can be found in the supporting information (Figure S6‐S21). The phenolic protons appear at δ = 11.41, 13.42 ppm and δ = 10.25, 13.20 ppm in the 1 H NMR spectra of Schiff bases H 2 L and H 2 L′ respectively . The signal for these protons are disappeared in the 1 H NMR spectra of all complexes indicating complete deprotonation of the ligands in complexes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Detailed NMR data of 1 – 3 are provided in the experimental section and NMR spectra can be found in the supporting information (Figure S6‐S21). The phenolic protons appear at δ = 11.41, 13.42 ppm and δ = 10.25, 13.20 ppm in the 1 H NMR spectra of Schiff bases H 2 L and H 2 L′ respectively . The signal for these protons are disappeared in the 1 H NMR spectra of all complexes indicating complete deprotonation of the ligands in complexes.…”
Section: Resultsmentioning
confidence: 97%
“…Solvents were distilled prior to use. The ligand H 2 L and H 2 L′ were synthesized according to literature procedures …”
Section: Methodsmentioning
confidence: 99%
“…The polydendate and potentially bridging Schiff base ligand ( H 2 L ) was prepared by the Schiff condensation of stoichiometric amounts of salicylaldehyde and 2‐amino‐4‐nitrophenol following a literature procedure . Pure orange crystals of H 2 L were treated with nickel nitrate hexahydrate in DMF using triethylamine as base at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, recently, we have reported a tetra‐nuclear Ni complex with a Ni 4 O 4 cubane core obtained with the Schiff‐base ligand N ‐(2‐hydroxyphenyl)‐3‐methoxy‐salicylideneamine . As a continuation of this project, we have studied the use of another Schiff base ligand (E)‐2‐(2‐hydroxybenzyliden)amino‐4‐nitrophenol ( H 2 L ) which can be synthesized from salicylaldehyde and 2‐amino‐4‐nitrophenol . The neutral ligand and its deprotonated form are shown in scheme .…”
Section: Introductionmentioning
confidence: 99%
“…[ 57–61 ] Many experimental and theoretical studies have indicated that ESIPT dynamics closely associated with the properties of substituent and their substituted position. Douhal et al [ 62,63 ] found that the ESIPT processes in 5‐amino‐2‐(2‐hydroxyphenyl)benzoxazole (5A‐HBO) could be fine‐tuned by the substituted position of NH 2 group on the benzoxazole. Li et al [ 47 ] reported the effect of various substituent on ESIPT process of 1‐(Acylamino)‐anthraquinons compounds.…”
Section: Introductionmentioning
confidence: 99%